2018
DOI: 10.1186/s12885-018-4888-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact of absolute lymphocyte counts for progression-free survival in human epidermal growth factor receptor 2-positive advanced breast cancer treated with pertuzumab and trastuzumab plus eribulin or nab-paclitaxel

Abstract: AbstractsBackgroundAlthough peripheral blood-based parameters (PBBPs) are reported as prognostic indicators in patients with breast cancers, their utility has not been studied in human epidermal growth factor receptor 2 (HER2)-positive advanced breast cancer (ABC). Tumor-infiltrating lymphocytes (TILs) might be a predictive factor in patients with HER2-positive ABC treated with pertuzumab and trastuzumab (PT) plus docetaxel. We aimed to evaluate whether PBBPs could have predictive value in HER2-positive ABC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…Given that clinicians have been greatly concerned with predicting prognosis through easily available biomarkers, numerous studies have investigated the association between NLR and prognosis among patients with breast cancer receiving chemotherapy [16,17]. Although ALC has received less attention than NLR in this perspective [22], our study has shown that ALC was significantly and independently associated with PFS among metastatic patients with breast cancer receiving eribulin. As mentioned previously, eribulin can activate Patients with ALC ≥1,500/μL had significantly better PFS than those with ALC < 1,500/μL (a; p = 0.013), whereas those with NLR ≥5.0 had significantly worse PFS than those with NLR < 5.0 (b; p = 0.020).…”
Section: Discussionmentioning
confidence: 66%
“…Given that clinicians have been greatly concerned with predicting prognosis through easily available biomarkers, numerous studies have investigated the association between NLR and prognosis among patients with breast cancer receiving chemotherapy [16,17]. Although ALC has received less attention than NLR in this perspective [22], our study has shown that ALC was significantly and independently associated with PFS among metastatic patients with breast cancer receiving eribulin. As mentioned previously, eribulin can activate Patients with ALC ≥1,500/μL had significantly better PFS than those with ALC < 1,500/μL (a; p = 0.013), whereas those with NLR ≥5.0 had significantly worse PFS than those with NLR < 5.0 (b; p = 0.020).…”
Section: Discussionmentioning
confidence: 66%
“…We identified eight studies with data on NLR as a prognostic factor in patients with metastatic BC [54][55][56][57][58][59][60][61]. Four articles (50%) enrolled patients with all molecular subtypes [54,[56][57][58], two focused on patients with HER2-positive BC [55,61], one on patients with TNBC [60] and one on patients with hormone receptor-positive BC receiving hormone therapy as initial treatment [59] (Table 5).…”
Section: Patients With Advanced Breast Cancermentioning
confidence: 99%
“…In these studies, the NLR cut-off value ranged from 1.9 to 3 (always based on previous studies), and the number of enrolled patients varied between 34 and 171. Six studies (75%) reported data on Asian populations [54][55][56]58,59,61]. Table 5.…”
Section: Patients With Advanced Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, two recent studies showed the different results concerning the relationship between absolute lymphocyte account and disease progression in HER2-positive BC [2,17]. In this study, we retrospectively analyzed the NLR as the predictive factor of 843 HER2-positive BC patients with or without trastuzumab treatment.…”
Section: Introductionmentioning
confidence: 99%